Antifungal evaluation of traditional herbal monomers and their potential for inducing cell wall remodeling in Candida albicans and Candida auris. Issue 3 (15th March 2020) - Liu, Juanjuan; Li, Qianqian; Wang, Changzhong; Shao, Jing; Wang, Tianming; Wu, Daqiang; Ma, Kelong; Yan, Guiming; Yin, Dengke
Abstract: Traditional herbal monomers (THMs) are widely distributed in many traditional Chinese formulas (TCFs) and decoctions (TCDs) and are frequently used for the prevention and treatment of fungal infections. The antifungal activities of five common THMs, including sodium houttuyfonate (SH), berberine (BER), palmatine (PAL), jatrorrhizine (JAT) and cinnamaldehyde (CIN), and their potential for inducing cell wall remodeling (CWR), were evaluated against Candida albicans SC5314 and Candida auris 12372. SH/CIN plus BER/PAL/JAT showed synergistic antifungal activity against both Candida isolates. Furthermore, SH-associated combinations (SH plus BER/PAL/JAT) induced stronger exposure of β-glucan and chitin than their counterparts, while CIN triggered more marked exposure compared with CIN-associated combinations (CIN plus BER/PAL/JAT). Collectively, this study demonstrated the anti- Candida effect and the CWR induction potential of the five THMs and their associated combinations, providing a possibility of their in vivo application against fungal-associated infections.